Review of mitigation technologies for terrestrial power grids against space weather effects. (November 2016) - Johnson, Michael; Gorospe, George; Landry, Jonathan; Schuster, Anja
Highlights: This paper discusses some of the earth-based effects of solar weather. Large-scale solar activity can adversely affect terrestrial power grids. We review terrestrial power grids and their susceptibility to such phenomena. We review mitigation and protection techniques for terrestrial power grids. Abstract: This paper discusses the earth-based effects of solar weather and presents a review of mitigation and protection techniques for the terrestrial power grid infrastructure. Solar events such as Coronal Mass Ejections (CMEs), solar flares and associated recombination events are one of the driving factors in space weather and the solar wind intensity. Even though it is located at such a great distance from our nearest star, the Earth and its associated satellites are still directly affected by variances in these space weather phenomena. On the surface of the planet, nowhere is this more immediate and important than with the terrestrial power grid, which is responsible for delivering electrical power to much of the planets population. Large-scale variations in solar activity can result in potentially devastating effects on the terrestrial power grid and the associated infrastructure. A team project was undertaken at the International Space University (ISU) Space Studies Program (SSP) 2013 to categorize and mitigate the risks involved in such a solar event. As part of this research, which included risk assessment for satellite, spacecraft and terrestrial resources, this paper presents a review of the terrestrial power grid and its inherent susceptibility to such phenomena. Mitigation schemes, techniques and approaches ranging from adaption of the existing power grid to alternative systems are considered in this paper, which allow for continued electrical power delivery and transmission, even in the face of such detrimental space weather effects.